Coagulation Factor XIIIA Subunit Missense Mutations Affect Structure and Function at the Various Steps of Factor XIII Action. Issue 10 (21st August 2016) - Thomas, Anne; Biswas, Arijit; Dodt, Johannes; Philippou, Helen; Hethershaw, Emma; Ensikat, Hans Juergen; Ivaskevicius, Vytautas; Oldenburg, Johannes
Abstract : This image corresponds to the work done by Biswas et al. on causality determination of FXIIIA subunit missense mutations reported in patients with mild FXIII deficiency. The lower part of the image shows the structural distribution of these missense mutations within the crystal structures of the zymogenic (left bottom) and non‐proteolytically activated FXIIIA subunit forms (right bottom). The structures are presented in ribbon format with individual domains colored and identified separately on symmetrical monomers. The mutations themselves are represented as their van der wal spheres. These mutations affect different aspects of FXIIIA subunit structure and function eventually resulting in altered clot thickness as shown by comparative scanning electron micrograph representation of their resulting clots in the top half of the image. ABSTRACT: Inherited defects of coagulation Factor XIII (FXIII) can be categorized into severe and mild forms based on their genotype and phenotype. Heterozygous mutations occurring in F13A1 and F13B genes causing mild FXIII deficiency have been reported only in the last few years primarily because the mild FXIII deficiency patients are often asymptomatic unless exposed to some kind of a physical trauma. However, unlike mutations causing severe FXIII deficiency, many of these mutations have not been comprehensively characterized based on expression studies. In our current article, we have transiently expressed 16 previously reported missense mutations detected in the F13A1 gene of patients with mild FXIII deficiency and analyzed their respective expression phenotype. Complimentary to expression analysis, we have used in silico analysis to understand and explain some of the in vitro findings. The expression phenotype has been evaluated with a number of expression phenotype determining assays. We observe that the mutations influence different aspects of FXIII function and can be functionally categorized on the basis of their expression phenotype. We identified mutations which even in heterozygous form would have strong impact on the functional status of the protein (namely mutations p.Arg716Gly, p.Arg704Gln, p.Gln602Lys, p.Leu530Pro, p.His343Tyr, p.Pro290Arg, and p.Arg172Gln ).